Epidemiology of traumatic injuries in the elderly patients: A descriptive study from a developing country - Behnam Panjavi; Saeed Shakiba; Khashayar Afshari; Farbod Yousefi; Saeed Reza Mehrpour; Mohammad Sadeq Najafi; Mohammad Hossein Nabian (Acta Medica Iranica, 2020)
The epidemiology of traumatic injuries in elderly patient fractures varies widely among countries. There is quantitative information to determine the prevalence and gender/age distribution of traumatic injuries in the elderly patient. The aim of the current study was to reveal the prevalence and age and gender distribution of various traumatic injuries in an elderly patient refers to as a tertiary orthopedic hospital in Iran. In a prospective descriptive study, all elderly patients with traumatic injuries attending the Orthopedic Trauma Unit of our center in 2001-2011 were included. Demographic details, the cause of injury, injury classification was recorded. For each gender, we calculated the numbers with fractures, dislocations, soft tissue injuries, ligamentous injuries, and lacerations and derived average age and gender-specific prevalence. During a period of 10 years, a total of 1172 elderly patients were admitted, 588 (50.1%) males, and 584 (49.9%) females. 849 patients (72.4%) had fractures. 323 (27.5%) of the patient had other limb injuries were include soft tissue injuries, lacerations, ligamentous injuries, and dislocations. The three most common fracture sites were proximal femur (40.02%), distal radius/ulna (12.47%), and proximal humerus (6.53%). The most prevalent traumatic injury among the elderly was fractures with a higher rate in females. The most common fracture sites were proximal of the femur and distal of radius and ulna bones.